2010
DOI: 10.1186/1471-2334-10-220
|View full text |Cite
|
Sign up to set email alerts
|

Predictors of persistently positive Mycobacterium-tuberculosis-specific interferon-gamma responses in the serial testing of health care workers

Abstract: BackgroundData on the performance of Mycobacterium-tuberculosis-specific interferon-(IFN)-γ release assays (IGRAs) in the serial testing of health care workers (HCWs) is limited. The objective of the present study was to determine the frequency of IGRA conversions and reversions and to identify predictors of persistent IGRA positivity among serially tested German HCWs in the absence of recent extensive tuberculosis (TB) exposure.MethodsIn this observational cohort-study HCWs were prospectively recruited within… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

9
55
1
4

Year Published

2010
2010
2023
2023

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 76 publications
(69 citation statements)
references
References 37 publications
9
55
1
4
Order By: Relevance
“…The extent of within-subject variability that we determined approximates the proposed borderline zones. Three recent serial testing studies among German and Portuguese HCWs demonstrated that the implementation of a QFT borderline zone of 0.2 to 0.7 IU/ml may safely reduce the rate of inconsistent results (26,29,31). For the T-SPOT, evidence for the safety of a specific borderline zone is sparse.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The extent of within-subject variability that we determined approximates the proposed borderline zones. Three recent serial testing studies among German and Portuguese HCWs demonstrated that the implementation of a QFT borderline zone of 0.2 to 0.7 IU/ml may safely reduce the rate of inconsistent results (26,29,31). For the T-SPOT, evidence for the safety of a specific borderline zone is sparse.…”
Section: Discussionmentioning
confidence: 99%
“…The present study was conducted at the University Hospital Bergmannsheil in Bochum, Germany, between July 2010 and February 2011. All IGRAs were performed at the Pulmonary Research Laboratory by a team with profound experience in IGRA research (26,27). Eligible HCWs were recruited prospectively by an occupational physician.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…However, use of the more sensitive QFT-GIT test in the present study diagnosed 25% of subjects with LTBI; this proportion is very much higher than that of the general population [22]. A recent systematic review of the utility of IGRA assays used to screen HCW for TB showed that the initial positivity rate was 1.3-31.0%; the analysis included data from countries where the incidence of TB is high [7]. Such variation is attributable to differences in sample sizes and the backgrounds of HCW among the studies; the extent of involvement and contact with TB patients, administration of chemo-prophylaxis, and years of work with TB patients, will have varied significantly among the studies.…”
Section: Discussionmentioning
confidence: 99%
“…One practical way to control TB is routine screening of HCW for latent tuberculosis infections (LTBIs) and administration of chemoprophylaxis to HCW suspected to have LTBIs. Therefore, evaluation of Mycobacterium tuberculosis (Mtb) infective status is crucial in HCW working in hospitals dedicated to TB patients [2,7,8]. In such contexts, screening of HCW should be routine and data should be evaluated longitudinally [2,9].…”
Section: Introductionmentioning
confidence: 99%